PENGARUH INTELLECTUAL CAPITAL DAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN ( Studi Kasus Perusahaan Perbankan Terdaftar Di BEI Periode Tahun 2018 – 2022 ) - Ita Aprita; Purwanti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
The company's financial performance reflects the company's credibility and capabilities, thereby providing a sense of trust in its users. This causes the Company's Financial Performance to become a very crucial issue in terms of trust so that all companies compete to provide the best service. Intellectual Capital and Corporate Governance are believed to be one of the things behind the changes in the company's financial performance that occur. This research aims to measure whether the influence of Intellectual Capital and Corporate Governance can influence the Company's Financial Performance. The population in this research are banking companies registered on the IDX for the 2018-2022 period. Research data uses secondary data using purposive sampling as a sampling method. The data analysis method used is multiple linear regression analysis of SPSS software. The results found that Intellectual Capital partially influences financial performance, in contrast to Good Corporate Governance which has no influence on financial performance. However, Intellectual Capital and Good Corporate Governance partially influence financial performance. Keywords: Intellectual Capital , Corporate Governance, Financial Performance Company.